A nationwide, multihospital, cross-sectional, self-reported study: Knowledge, attitude and behaviour concerning the use of personal protective equipment among healthcare workers during the COVID-19 pandemic in Malaysia - Haniza, Sahdi; Nurul Fatiha, Zuraidi; Khairul Imran, Redzuan Hafiz Boon; Dayang Nurul Alwani, Abang Ahmad Zaini; Mohd Suhaimi, Ramlee (Malaysian Medical Association, 2023)
Introduction: Personal protective equipment (PPE) is crucial in reducing the risk of hospital-acquired COVID-19 as health care workers (HCW)s are highly exposed to the virus during the management of patients with COVID-19. This study assesses the knowledge, attitude and behaviour of the HCWs towards the use of PPE during the COVID-19 pandemic in Malaysia.